Biological and behavioral responses of European honey bee (Apis mellifera) colonies to perfluorooctane sulfonate exposure. (18th May 2021) - Sonter, Carolyn A.; Rader, Romina; Stevenson, Gavin; Stavert, Jamie R.; Wilson, Susan C.
Abstract: Bees provide pollination services to managed and wild ecosystems but are threatened globally due to multiple stressors, including exposure to contaminants. Perfluorooctane sulfonate (PFOS) is a widely detected and persistent contaminant that accumulates and biomagnifies in food chains. In this exposure effect study, small whole colonies of Apis mellifera (1000 bees) were exposed to PFOS using a purpose‐built cage system over a 4‐week period. The PFOS exposure concentrations were provided to bees in sugar syrup at concentrations detected in the environment, ranging from 0 to 1.6 mg L −1 . A range of biological and behavioral responses were monitored. Bee tissue, honey, and fecal matter were analyzed using isotope dilution combined with liquid chromatography–tandem mass spectrometry adapted for bee and honey matrix analysis. Bee mortality increased significantly with PFOS exposure at 0.8 mg L −1 or greater, and brood development ceased entirely at 0.02 mg L −1 or greater. Colony activity, temperament, hive maintenance, and defense were adversely affected in all PFOS exposure treatments compared with the control, even at the lowest PFOS exposure of 0.02 mg L −1 . Perfluorooctane sulfonate was detected in bee tissue with a mean bioaccumulation factor of 0.3, and it was also identified in honey and in feces collected from the hive cages. These findings provide the first evidence that PFOS exposure adversely affects honey bee colonies and may transfer to honey. With PFOS contaminating thousands of sites worldwide, our study has implications for exposed bee populations under natural conditions, pollination services, the honey industry, and human health. Integr Environ Assess Manag 2021;17:673–683. © 2021 SETAC KEY POINTS: The first evidence that PFOS exposure adversely affects honey bee colonies with significant impacts observed in brood production, worker bee mortality, behavior, and temperament. Evidence that PFOS accumulates in honey bee tissue and may transfer to honey when bees are exposed through diet.